(untitled) (Archaeologia Adriatica, 2018)
During the two seasons of rescue archaeological excavations at the hillfort site of Brekinjova Kosa, the remains of an Early Medieval structure (probably a church) and Early Medieval burials containing rich grave goods were recorded. The most remarkable feature is a rich burial within the structure (grave 4) whose grave goods put it among the richest Early Medieval graves so far excavated on the territory of modern-day Croatia. Apart from the finds within the graves themselves, a certain amount of Early Medieval pottery shards were recorded at the site. The area surrounding the site is mostly archaeologically unresearched and today sparsely populated, but this type of find bears witness to its importance in the Early Middle Ages.